O091 Social deprivation and malignant progression of anal intraepithelial neoplasia. (22nd July 2022) - Hinchcliffe, Z; Soliman, F; Hargest, R
Abstract: Introduction: Social deprivation is known to be a risk factor for cervical cancer but its influence on progression rate to invasive cancer is less clear. This study aimed to investigate whether deprivation was a risk factor for high grade anal intra-epithelial neoplasia (AINIII) progression to anal squamous cell carcinoma (ASCC). Methods: Retrospective analysis of AINIII patients in Southeast Wales between 2000–2021. Deprivation was calculated from postcodes at time of referral, divided into five quintiles (Welsh Index of Multiple Deprivation 2019). Welsh Clinical Portal and Cancer Network Information System Cymru (CaNISC) were utilised to collect patient demographics, histopathology and clinical outcomes. Results: Eighty-six AINIII patients were identified. Twenty-nine presented with synchronous ASCC and AINIII. Thirteen progressed to cancer (median 23 months). The proportion of patients in each deprivation quintile was calculated. The association between deprivation and incidence of ASCC at presentation ( p =0.93) and AIN transformation to ASCC ( p =0.65) were not statistically significant (chi-square analysis). Conclusion: No correlation between presentation of anal ASCC or AINIII progression and social deprivation was observed. Due to small sample size, multicentre research is required to investigate this further. Take-home message: Social deprivation was not observed to be a risk factor for anal Intra-epithelial Neoplasia III or anal cancer in our cohort. However, further research across a larger sample size is required to investigate this association further.